Implementation of Multicultural Education in Islamic Boarding School-Based Education: A Study of Student Dormitory Life at Darul Fikri Islamic Boarding School in Sidoarjo - Aulia Rahma; Isa Anshori (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2026)
Multicultural education is an essential need in educational environments characterized by social and cultural diversity, including Islamic boarding schools (pesantren). As religious-based educational institutions, pesantren possess distinctive characteristics in managing students from diverse regional, cultural, and backgrounds. This study aims to examine the implementation of multicultural educational values at Darul Fikri Islamic Boarding School in Sidoarjo, focusing on students’ dormitory life, the role of educators, and the challenges encountered in the process. This study employed a qualitative case study design. Data were gathered through observation and in-depth interviews with administrators and educators, then analyzed using data condensation, presentation, and conclusion drawing. The findings reveal that multicultural values are internalized through heterogeneous dormitory life and structured mentoring. Specifically, the study finds that strategic room allocation, which mixes students across classes, effectively prevents social exclusivism. The dual role of educator, particularly Ustadz Kardi as both supervisor and administrator, ensures consistent modeling of tolerance. Despite regional language barriers, continuous guidance enables students to adapt and build inclusiveness, as natural social practices in dormitories are more effective than formal instruction in fostering multiculturalism.